The initiation of labor and hormonal control, oxytocin action 17b estradiol and progesterone inhibiting effect - Pinto, Roberto (2015)
To date clinical research on the initiation of labor could not clarify what was the factor or factors that put into action the uterine contractile system. Pharmacological means demonstrated participating in a manner similar to the physiology in stimulating uterine contraction, only appeared in the world, oxytocin, neurohormone composed of eight amino acids whose mother substance is produced by the hypothalamus and is stored and secreted by the posterior lobe of the pituitary.